Factors Affecting Covid-19 Disease Prevention Behavior in Bandar Lampung, Indonesia - Nova Nurwinda Sari; Annisa Agata; Armen Patria (Journal for Quality in Public Health, 2020)
Coronavirus Disease 19 or what we know as Covid-19 is a disease caused by coronavirus that can cause respiratory infections with mild to severe symptoms. Covid-19 disease can be prevented by the community if the community implements covid prevention measures such as using masks, diligently washing hands and keeping a distance. Preliminary preliminary survey note that the majority of respondents have not implemented the co-19 prevention behavior properly. The purpose of this study was to analyze factors that influence co-19 prevention behavior in Bandar Lampung. This research is a quantitative study with a descriptive analytic cross sectional design. The population and research sample using cluster sampling namely using 10 regions included in the Bandar Lampung area of ​​100 respondents. The research instrument used questionnaire sheets that had been tested for validity. Data analysis using chi square test. The results obtained data that there is a relationship between age (p-value 0.017), there is no gender relationship (p-value 0.878), there is a relationship between the level of education (p-value 0.000), there is a relationship of knowledge about covid-19 (p-value 0.029) with covid-19 disease prevention behavior in Bandar Lampung. The conclusion is that factors related to co-19 disease prevention behavior are age, education level, and knowledge of co-19. Suggestions should provide information about co-19 and the importance of co-19 prevention behavior continue to be given to the public. Keywords: Predisposing Factors, Behavioral Prevention, Covid-19